1977
DOI: 10.1128/jvi.21.3.950-955.1977
|View full text |Cite
|
Sign up to set email alerts
|

Lipids of rabies virus and BHK-21 cell membranes

Abstract: MATERIALS AND METHODS Virus strain and propagation. The Flury highegg-passage (HEP) strain of rabies virus was propagated in BHK-21 cells and concentrated by previously published methods (28), except that the maintenance medium used for virus propagation contained 0.2% (vol/vol) "fatty acid poor" bovine serum albumin (Miles Laboratories, Inc., Elkhart, Ind.) as the only protein supplement to permit unrestricted lipid synthesis (7). With this technique, as with influenza virus, there was no loss of viral infect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1981
1981
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…As demonstrated by the following calculation for CHO membranes, contaminating membranes with a lower content of SM (ER) and those with a higher content of SM (plasma membrane and endosomes/lysosomes) roughly compensate for each other. To assess the influence on the measured value for SM in donor fractions of contaminating membranes, we used the data given in Table III, in conjunction with the SM contents reported for plasma membranes and endosomes/lysosomes (14-18 mol%) (Cezanne et al, 1992;Warnock et al, 1993), as well as ER membranes (10 mol%) (Blough et al, 1977;Brotherus and Renkonen, 1977;Urade et al, 1988). The calculations were made based on an SM content of 18 mol% for plasma membranes, the highest value reported.…”
Section: Determination Of the Extent Of Lipid Segregationmentioning
confidence: 99%
“…As demonstrated by the following calculation for CHO membranes, contaminating membranes with a lower content of SM (ER) and those with a higher content of SM (plasma membrane and endosomes/lysosomes) roughly compensate for each other. To assess the influence on the measured value for SM in donor fractions of contaminating membranes, we used the data given in Table III, in conjunction with the SM contents reported for plasma membranes and endosomes/lysosomes (14-18 mol%) (Cezanne et al, 1992;Warnock et al, 1993), as well as ER membranes (10 mol%) (Blough et al, 1977;Brotherus and Renkonen, 1977;Urade et al, 1988). The calculations were made based on an SM content of 18 mol% for plasma membranes, the highest value reported.…”
Section: Determination Of the Extent Of Lipid Segregationmentioning
confidence: 99%
“…Although initial clinical trials have demonstrated that azidothymidine may prolong life in certain AIDS patients [Chaisson et al, 1986;Yarchoan et al, 1986Yarchoan et al, , 1987Fischl et al, 19871, the high degree of toxicity observed with all reverse transcriptase inhibitors precludes their widespread use and illustrates the need for efficacious compounds with a higher safety margin [Barnes, 1986;Richman et al, 1987;Vogt and Hirsch, 19871. Another approach to developing antiviral agents involves manipulation of viral membrane lipids Klepner et al, 19871. Lipid composition has been determined for several viruses [Blough, 1968;Blough and Larson, 1968;Klenk and Choppin, 1969;David, 1971;McShany and Wagner, 1971;Renkonen et al, 1972;Blough et al, 1977;Barnes et al, 19871. The membranes of enveloped viruses are usually lipid bilayers containing specific proteins essential for viral attachment, penetration, and infection of cells [Lenard and Compans, 19741.…”
Section: Introductionmentioning
confidence: 99%
“…Of the 40 samples examined, 36 tested positive for IFD (90%) and 33 (82.5%) for RT-PCR. In an inter-laboratory test as a tool to increase animal rabies diagnostic capabilities in veterinary laboratories in sub-Saharan Africa, RT-PCR had a sensitivity of 96.7% and specificity of 100%, both higher than those obtained by [16] with IFD (89.2% and 86.2%, respectively). Manisha Biswal and al showed 100% sensitivity and specificity to RT-PCR, compared to 83.3% to IFD.…”
Section: Ddl Moyenne Des Carrés Détection Des Virusmentioning
confidence: 92%